Synergistic effects of soybean oligosaccharides and Chlorella pyrenoidosa on water quality and microbial community structure in biofloc system - Zhou, Hangxian; Lou, Mengsha; de Cruz, Clement; Wei, Jie; Tao, Mingwei; Zhao, Jianhua; Zhang, Rongfei; Xu, Qiyou (Springer Science and Business Media Deutschland GmbH, 2025)
This study explored the synergistic effects of soybean oligosaccharides (SBOS) and Chlorella pyrenoidosa (C. pyrenoidosa) on water quality and microbial community structure of aquaculture effluent in a biofloc system. Five treatments (5 replicates, C/N = 15) were tested for 9 days: CON group (control, no treatment), GLU group (glucose), SBOS group (2.5% SBOS and 97.5% glucose), CP group (glucose and C. pyrenoidosa), and CS group (2.5% SBOS, 97.5% glucose and C. pyrenoidosa). C. pyrenoidosa concentration was 5.37 × 105 cells/mL. On day 1, nitrate nitrogen and total nitrogen in CP and CS groups were significantly lower than GLU group; on day 5, ammonia nitrogen content in CS group was significantly lower than others experimental groups; on day 7, nitrite nitrogen content in CP and CS groups was significantly lower than others experimental groups (P < 0.05); on day 3 biofloc volume (FV) in CS group showed a significant increase compared to CON and GLU groups (P < 0.05). All experimental groups reduced turbidity compared to CON group (P < 0.05). SBOS and C. pyrenoidosa demonstrated significant synergistic effects on water quality and biofloc formation: nitrite reduction (day 1), increased FV (day 3), and nitrate reduction (days 5 and 7) (P < 0.05). Compared with other experimental groups, the abundance of Aeromonadaceae decreased significantly, and Bacillus and Mycobacteria increased significantly in CS group, enhancing nitrogen cycling and organic matter degradation pathways (P < 0.05). These findings suggest that SBOS and C. pyrenoidosa exhibit synergistic effects in treatment of effluent in biofloc system, and efficiently remove nitrogen and optimize microbial community structure.